منیراحمدبادینی ءِ آزمانکانی ازمی وانشت - Ahmed, Aziz; Dad, A.R (Hanken, 2018)
Munir Ahmed Badeni is one of best fiction writers of Balochistan. He has written more then hundred novels and a considerable number of short stories in Baloch literature. Munir Ahmad Badeni, got fame through his novels instead of his short stories. Particularly, this research paper finds out the different themes of Badini’s short stories.